A digital current controller based on active resistance term feedback for SPMSM drives - Yuan, Xin (2022)
Improving the control performance of surfacedmounted permanent magnet synchronous machine (SPMSM) drives, digital current controllers with active resistance term feedback (ARTF) based on an exact zero-order hold (ZOH) equivalent discrete SPMSM model have been developing. Derived from the ARTF structure, few approaches are developed to suppress the ARTF delay effect on the digital current controller. To fill this gap, an improved digital current controller with the proposed digital internal mode control (IMC) current estimator is designed. In the proposed structure, the predicted current can be effectively utilized as the ARTF delay compensation and feedback of the current controller at the same time. Compared with other state-of-the-art digital current controllers with ARTF, the performance evaluation of dynamic response, disturbance rejection and parameter robustness is originally carried out based on the exact ZOH equivalent discrete SPMSM model. Furthermore, the experimental results are able to fully verify the correctness of the proposed method.